Operating strategies for variable-flow sequencing batch reactors. - Bungay, S.; Humphries, M.; Stephenson, Tom (Blackwell Publishing, 2007)
Sequencing batch reactors (SBRs) are variable-volume, non-steady-state, suspended-growth biological wastewater treatment reactors. The treatment process is characterised by a repeated treatment cycle consisting of a series of sequential process phases: fill, react, settle, decant and idle. The design and operation of an SBR must take into account (1) the biological process requirement for treating influent wastewater and (2) the hydraulic requirement to enable throughput of the water through the reactor without compromising on the quality of biological treatment. During routine operation, the priority between the process and hydraulic consideration can change depending on the influent flow rate and its rate of change. The importance of the interaction between these considerations will vary depending on the fill strategy and the cycle time control strategy. Where flow-proportional cycle times are utilised to optimise the treatment process, the operating strategy must be capable of accurately adjusting the intercycle phase times to prevent loss of biological treatment or volumetric capacity. This paper considers various operating strategies and describes the specific strategy used at the SBR at Avonmouth wastewater treatment works.
Keywords: Cycle time; flow proportional; hydraulic consideration; process consideration; variable flow